Does Transition to Retirement Promote Grandchild Care? Evidence From Europe - Tanskanen, Antti O.; Danielsbacka, Mirkka; Hämäläinen, Hans; Solé-Auró, Aïda (Frontiers in Psychology, 2021)
Evolutionary theory posits that grandparents can increase their inclusive fitness by investing in their grandchildren. This study explored whether the transition to retirement affected the amount of grandchild care that European grandparents provided to their descendants. Data from five waves of the longitudinal Survey of Health, Ageing, and Retirement in Europe collected between 2004 and 2015 from 15 countries was used. We executed within-person (or fixed-effect) regression models, which considered individual variations and person-specific changes over time. It was detected that transition to retirement was associated with increased grandchild care among both grandmothers and grandfathers. However, the effect of retirement was stronger for grandfathers than for grandmothers. Moreover, transition to retirement was associated with increased grandchild care among both maternal and paternal grandparents, but there was no significant difference between lineages in the magnitude of the effect of transition to retirement on grandchild care. In public debate retirees are often considered as burden to society but the present study indicated that when grandparents retire, their investment in grandchildren increased. The findings are discussed with reference to key evolutionary theories that consider older adults’ tendency to invest time and resources in their grandchildren.